PELAKSANAAN PELAYANAN KESEHATAN DI PUSKESMAS SEI BAUNG KECAMATAN ILIR BARAT I KOTA PALEMBANG - Sutinah Andaryani (Jurnal Pemerintahan dan Politik, 2022)
This research was a qualitative research by using a descriptive research approach with a case study design. The purpose of this study was to find out the health services at the Community Health Center of Sungai Baung, District of Ilir Barat I, Palembang. The interview, observation and documentation were used in collecting data. Then, the data were analysed by using source triangulation techniques, methods and theories. The results of the study found that the Community Health Center of Sungai Baung had complete and adequate health facilities as well as the supporting physical facilities. They were Maternal and Child Health Services, treatment, counseling, laboratory services, health promotions, and mobile health centers (PUSLING), administrative facilities, services, laboratories, medicines, waiting rooms, and adequate, clean and tidy parking lot. Moreover, the officers who provided services were also reliable and had good abilities, because they were graduates from various well-known universities which were qualified in the field of health. The officers also had good responsiveness in providing information and handling complaints from patients. They also provided a guarantee of service for patients and they carried out their duties based on standard health care procedures. Furthermore, in providing services, a good communication was established between officers and patients as the recipients of health servicesKeywords: Implementation, Health Services, Community Health Center of Sungai Baung